2021
DOI: 10.26418/jebik.v10i2.47461
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Karakteristik Perusahaan, Kinerja Perusahaan, Dan Management Entrenchment Terhadap Manajemen Laba

Abstract: The purposes of this study is to investigate the impact of firm characteristics, firm performances, and management entrenchment on earnings management by using firms registered on Bursa Efek Indonesia for the period 2015-2019. Sampling method that is used in this study is purposive sampling method so the objects should meet the criteria. The exception sample for this study is financial firms due to differences on some regulations of reporting and firms without complete annual and financial report published for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Semakin besar ukuran perusahaan akan menunjukkan tanda positif kepada pihak eksternal, khususnya investor, untuk melakukan investasi modal di perusahaan yang mengakibatkan pemakaiaan dana eksternal mengalami peningkatan, yang akan membuat manajer meminimalkan tindakan manajemen laba karena perusahaan berukuran besar menjadi pusat perhatian bagi publik yang berkepentingan. Penelitian ini sesuai dengan hasil penelitian Prajitno & Vionita (2020) dan Tang & Fiorentina (2021) mengindikasikan bahwasanya ukuran perusahaan memiliki pengaruh negatif kepada manajemen laba.…”
Section: Komite_auditunclassified
“…Semakin besar ukuran perusahaan akan menunjukkan tanda positif kepada pihak eksternal, khususnya investor, untuk melakukan investasi modal di perusahaan yang mengakibatkan pemakaiaan dana eksternal mengalami peningkatan, yang akan membuat manajer meminimalkan tindakan manajemen laba karena perusahaan berukuran besar menjadi pusat perhatian bagi publik yang berkepentingan. Penelitian ini sesuai dengan hasil penelitian Prajitno & Vionita (2020) dan Tang & Fiorentina (2021) mengindikasikan bahwasanya ukuran perusahaan memiliki pengaruh negatif kepada manajemen laba.…”
Section: Komite_auditunclassified
“…Existing studies in Indonesia have studied CEO's demographic characteristics such as gender and age on firm's earning management (Putra, 2021;Putri & Rusmanto, 2019;Saputri, 2021), similar to some other studies regarding earnings management in other developing countries (Alqatamin et al, 2017;Enofe et al, 2017). There are also related studies in Indonesia focused on general characteristics of the company such as financial ratios and the size of the firm (S. Tang & Fiorentina, 2021) of the entire board such as board size dan the existence of independent commissioner (Setiawan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According Thio Lie Sha (2022), Tang & Fiorentina (2021), Hunah et al(2021), Leverage is debt used by the company in order to finance its assets to carry out the company's activities so that it can operate properly. When the debt owned by the company is getting bigger, the level of risk will also be getting bigger.…”
Section: Introductionmentioning
confidence: 99%
“…From the lead director's tenure in earnings management found that there are managers who are careful when they first hold high positions in management, and then as the year goes by they will become aggressive. When they have achieved earnings manipulation at the highest level, they will again be careful and report earnings in a non-aggressive manner (Tang & Fiorentina, 2021).…”
Section: Introductionmentioning
confidence: 99%